COMPARISON OF BIOLOGICAL PARAMETERS IN HOME-BASED AND TRAINING CENTER SETTINGS DURING THE PREPARATORY PHASE OF SITTING VOLLEYBALL PARA-ATHLETES FOR THE 2024 PARIS PARALYMPIC GAMES - Guedes, Ingrid Vitória Barnabé da Silva; Monteiro, Rafaella de Andrade; de Souza, Caroline de Cássia Batista; do Carmo, Vinícius José Guimarães; da Silva, Lucas Paulino; de Souza, Wesley Lemos Lira; da Silva, Betuel Gomes; Santos, Mariana Tereza de Albuquerque; da Silva, Pamella; Studart-Pereira, Luciana Moraes; Melo, Renato de Souza; Ferreira, Ana Paula de Lima (Seven Editora, 2026)
The objective of this study was to evaluate and compare the biological parameters of sitting volleyball para-athletes in home settings and during a training camp at a Training Center, during the preparatory phase for the 2024 Paris Paralympic Games. Data were collected using wearable technology (Garmin Forerunner 245® smartwatch) and Dual-Energy X-ray Absorptiometry (DXA), GE Healthcare®, Lunar Prodigy Advance. The sample consisted of 12 athletes from the Brazilian women’s sitting volleyball national team, who were monitored with the smartwatch over the 90 days preceding the 2024 Paris Paralympics. The parameters recorded included minimum (HRMIN) and maximum heart rate (HRMAX), average heart rate during training, resting, active, and total calories, body battery, daily stress level (DS), and body composition. The results showed that at the training center, athletes presented significantly higher HRMAX values (135 ± 10.7 bpm) and total calorie expenditure compared to the home setting (p < 0.05), and a direct correlation was identified between daily stress and body energy (r = 0.66; p = 0.02). Thus, greater energy expenditure was observed at the training center, related to the intensity of training sessions, an inverse correlation between energy recovery and physiological stress, and positive associations between total caloric expenditure and lean mass, as well as between caloric expenditure and fat mass.DOI: https://doi.org/10.56238/sevened2026.002-011